Assessment of the Level of Development of Internet Resources in Kazakhstan: Gender Aspect - D. M. Kangalakova; K. I. Ibragimova; S. Zh. Ibraimova; A. S. Nurbatsin (Экономика: стратегия и практика, 2022)
In recent years, in the pre-pandemic period, offline marketplaces are popular, and in the post-pandemic period, online marketplaces are becoming more popular. During the quarantine restriction, many enterprises began to adapt to online sales. The enterprise that was able to adapt remained active in the economy, and enterprises that were unable to adapt went bankrupt. Within the framework of this issue, the aim of the research article was to analyze the specifics of the interaction of Kazakhstani women entrepreneurs in online shopping. In the course of the study, in addition to scientific methods, the interviewing method was used. The interview was attended by 29 businesswomen from Almaty city. The business areas of women engaged in entrepreneurship included such areas as the trade in adult clothing, the sale of fabrics, fashion salons, and the sale of Korean cosmetics. The purpose of the interview is to identify the reasons, and features of the work of Kazakhstani women on online marketplaces and identify the advantages and disadvantages of trading on offline marketplaces. The results of the interview can be used to achieve efficiency in organizing the work of the online marketplace. In addition, knowing the views of women, the potential of women in the regions of the state can be used to formulate policies aimed at developing the economy. That is, with the help of online work of women, it is necessary to influence the unemployment rate in the regions, and increase the source of income and other quality of life.